Alantolactone is a natural product that potently inhibits YAP1/TAZ through promotion of reactive oxygen species accumulation. Issue 10 (6th August 2021) - Nakatani, Keisuke; Maehama, Tomohiko; Nishio, Miki; Otani, Junji; Yamaguchi, Keiko; Fukumoto, Miki; Hikasa, Hiroki; Hagiwara, Shinji; Nishina, Hiroshi; Mak, Tak Wah; Honma, Teruki; Kondoh, Yasumitsu; et al.
Abstract: Yes‐associated protein 1 (YAP1) and its paralogue PDZ‐binding motif (TAZ) play pivotal roles in cell proliferation, migration, and invasion, and abnormal activation of these TEAD transcriptional coactivators is found in diverse cancers in humans and mice. Targeting YAP1/TAZ signaling is thus a promising therapeutic avenue but, to date, few selective YAP1/TAZ inhibitors have been effective against cancer cells either in vitro or in vivo. We screened chemical libraries for potent YAP1/TAZ inhibitors using a highly sensitive luciferase reporter system to monitor YAP1/TAZ‐TEAD transcriptional activity in cells. Among 29 049 low‐molecular‐weight compounds screened, we obtained nine hits, and the four of these that were the most effective shared a core structure with the natural product alantolactone (ALT). We also tested 16 other structural derivatives of ALT and found that natural ALT was the most efficient at increasing ROS‐induced LATS kinase activities and thus YAP1/TAZ phosphorylation. Phosphorylated YAP1/TAZ proteins were subject to nuclear exclusion and proteosomic degradation such that the growth of ALT‐treated tumor cells was inhibited both in vitro and in vivo. Our data show for the first time that ALT can be used to target the ROS‐YAP pathway driving tumor cell growth and so could be a potent anticancer drug. Abstract : YAP1 and its paralogue TAZ play pivotal roles in cell proliferation, migration, and invasion, and abnormal activation of these TEAD transcriptional coactivators is found in diverse cancers in humans and mice. We screened chemical libraries for potent YAP1/TAZ inhibitors using a highly sensitive luciferase reporter system to monitor YAP1/TAZ‐TEAD transcriptional activity in cells. We found that alantolactone primarily targets the ROS‐YAP pathway driving tumor cell growth and so could be a potent anticancer drug.